Direct Electrodeposition of Nanogold on Gallium-Doped Zinc Oxide by Cyclic Voltammetry and Constant-Potential Techniques: Application to Electro-Oxidation of Sulfite. Issue 7 (8th April 2016) - Ahmed, Muhammad Ibrar; Aziz, Md. Abdul; Helal, Aasif; Shaikh, M. Nasiruzzaman
Abstract : Nanogold (NG) was directly electrodeposited onto the surfaces of gallium zinc oxide (GZO) electrodes by using cyclic voltammetry (CV) and constant-potential methods from an aqueous solution composed of 1 mM each of hydrogen tetrachloroaurate, sodium hydroxide and sodium sulfate. Different deposits were obtained by simply varying the cycle number when using CV and by varying the deposition potential when using the constant-potential method. The NG-modified GZO electrodes were characterized by scanning electron microscopy (SEM) and electrochemical methods. When using the CV method, gold nanoplates along with some spherical gold nanoparticles were directly grown on the electrode surface, with a quite uniform distribution. In contrast to the observations with the GZO substrate, only spherical gold nanoparticles were deposited on FTO using the same CV deposition method and same parameters. Applying a constant potential instead of CV yielded considerably more spherical gold nanoparticles than gold nanoplates on GZO, with only a few gold nanoplates when the NG on GZO was prepared at +0.2 V. This work has demonstrated a simple and effective way to control the shapes and sizes of NG particles on GZO. Furthermore the NG/GZO produced by the CV method showed good electrocatalytic properties toward the electro-oxidation of sulfite ion.